Family Empowerment Program to Improve Quality of Life in Thalassemia Patient: A Case Study - Andan Firmansyah; Neng Wiwin Mulyati; Henri Setiawan (Genius Journal, 2023)
Introduction: Thalassemia can cause major health problems in children and adversely affect their quality of life, which includes reduced physical, psychological, social, and educational functioning. A family empowerment program is a process or effort to increase the knowledge and willingness of families to maintain and improve the Quality Of Life of children with thalassemia Objective: The purpose of this case study is to carry out nursing care for children with thalassemia and quality of life problems with the Family Empowerment Program (FEP) approach. Method: The method used is descriptive-qualitative with a case study approach. As well as pre-test intervention and post-test intervention. Nursing care was carried out with the author for three days and the family intervened using the Family Empowerment Program (FEP) approach for three weeks. The subject of this case study is a thalassemia child with poor quality of life. Data collection techniques include interviews, observation, physical examination, and documentation. Results: The results of the case study at the assessment stage found that An.S. had problems in the dimensions of social function and school function due to complex or long-term treatment or treatment programs and unsatisfactory interpersonal interactions. Intervention and implementation used in An.S. are using family empowerment with the Family Empowerment Program (FEP) approach. Conclusion: The conclusion of nursing care in children with thalassemia was that during the intervention of three meetings, there were few changes that were positive for the family and the client in handling social function and school function. After the intervention of the Family Empowerment Program (FEP) approach for three weeks, the results of filling out the PedsQL questionnaire show that the dimensions of physical function are good (90.6), the dimensions of emotional function are good (95), the dimensions of social function are good (80) and the dimensions of school function are good (85).